192k views
2 votes
Tyler simplified the expression x Superscript negative 3 Baseline y Superscript negative 9. His procedure is shown below.

x Superscript negative 3 Baseline y Superscript negative 9 = StartFraction 1 Over x cubed EndFraction times StartFraction 1 Over y Superscript negative 9 EndFraction = StartFraction 1 Over x cubed y Superscript negative 9 EndFraction

What is Tyler’s error?

User Setheron
by
4.8k points

1 Answer

4 votes

Answer:


y^(-9)\\eq (1)/(y^(-9))

Explanation:

Tyler simplified the expression:
x^(-3)y^(-9) as shown below:


x^(-3)y^(-9)=(1)/(x^3)X (1)/(y^(-9))=(1)/(x^3y^(-9))

We notice that in Tyler's work:


y^(-9)= (1)/(y^(-9))

Whereas, the correct form would have been:


y^(-9)= (1)/(y^(9))

Making our solution:


x^(-3)y^(-9)=(1)/(x^3)X (1)/(y^(9))=(1)/(x^3y^(9))

User Vijay Yadav
by
4.5k points